OrchidBase 6.0: increasing the number of Cymbidium (Orchidaceae) genomes and new bioinformatic tools for orchid genome analysis - You-Yi Chen; Ye Sun; Chung-I Li; Shao-Ting Lin; Hao-Chen Zheng; Zhe-Bin Zhang; Bing-Ru Lee; Chun-Lin Hsieh; Yu-Yun Hsiao; Chi-Nga Chow; Chien-Wen Yang; Wen-Chi Chang; et al. (BMC Plant Biology)
Abstract Background Orchids are well-known for their rich diversity of species as well as wide range habitats. Their floral structures are so unique in angiosperms that many of orchids are economically and culturally important in human society. Orchids pollination strategy and evolutionary trajectory are also fantastic human for centuries. Previously, OrchidBase was created not only for storage and management of orchid genomic and transcriptomic information including Apostasia shenzhenica, Dendrobium catenatum, Phalaenopsis equestris, and two species of Platanthera that belong to three different subfamilies of Orchidaceae, but explored orchid genetic sequences for their function. The OrchidBase offers an opportunity for the plant science community to compare orchid genomes and transcriptomes, and retrieve orchid sequences for further study. Description Recently, three whole-genome sequences of the Epidendroideae species, Cymbidium sinense, C. ensifolium and C. goeringii, were sequenced de novo, assembled, and analyzed. In addition, the systemic transcriptomes of these three species have been established. We included these datasets to develop a new version of OrchidBase 6.0. Furthermore, four new analytical methods, namely regulation, updated transcriptome, advanced BLAST, and domain search, were developed for orchid genome analyses. Conclusion OrchidBase 6.0 extended genetic information to that of eight orchid species and created new tools for an expanded community curation in response to the ever-increasing volume and complexity of data.